Analisis Dampak Konflik Rusia-Ukraina terhadap Perdagangan Internasional Indonesia - Ani Fitriah; Ummi Kulsum; M.Hasan .; Muhammad As Rori; M. Dimas Aril Pramudita (CV. ITTC INDONESIA, 2025)
The Russia-Ukraine conflict, which has escalated since 2022, has significantly impacted the stability of global trade and the global economy, including Indonesia. This study aims to analyze how the conflict has impacted Indonesia's trade relations with Russia and Ukraine, particularly through energy price fluctuations, disruptions to the supply of strategic commodities, and changes in economic cooperation patterns.Specifically, this study examines how Indonesia's dependence on wheat imports from Ukraine and the opportunities for increasing exports of commodities such as crude palm oil (CPO), rubber, and other derivative products to both countries have changed amidst geopolitical tensions. This research uses a qualitative methodology based on desk research, examining official government reports, publications from international institutions, and literature related to the economic relations between Indonesia, Russia, and Ukraine. The analysis shows that although the contribution of trade between the two countries to Indonesia's total trade is relatively small, the indirect impacts of energy price spikes and commodity supply disruptions have significant implications for inflation, production costs, and the direction of economic cooperation. Furthermore, bilateral relations between Indonesia and Russia in the energy, defense, education, and infrastructure sectors exhibit new dynamics influenced by global geopolitical conditions. Therefore, this conflict impacts not only the trade balance but also Indonesia's long-term policy strategy and relationships in the international economic arena.